Neuropsychiatric Symptoms in Parkinson's Disease with Mild Cognitive Impairment and Dementia - Iracema Leroi; Hiranmayi Pantula; Kathryn McDonald; Vijay Harbishettar (Parkinson's Disease)
Neuropsychiatric symptoms commonly complicate Parkinson’s disease (PD), however the presence of such symptoms in mild cognitive impairment (PD-MCI) specifically has not yet been well described. The objective of this study was to examine and compare the prevalence and profile of neuropsychiatric symptoms in patients with PD-MCI (n = 48) to those with PD and no cognitive impairment (PD-NC, n = 54) and to those with dementia in PD (PDD, n = 25). PD-MCI and PDD were defined using specific consensus criteria, and neuropsychiatric symptoms were assessed with the 12-item Neuropsychiatric Inventory (NPI). Self-rated apathy, depression, and anxiety rating scales were also administered. Over 79% of all participants reported at least one neuropsychiatric symptom in the past month. The proportion in each group who had total NPI scores of ≥4 (“clinically significant”) was as follows: PD-NC, 64.8%; PD-MCI, 62%; PDD 76%. Apathy was reported in almost 50% of those with PD-MCI and PDD, and it was an important neuropsychiatric symptom differentiating PD-MCI from PD-NC. Psychosis (hallucinations and delusions) increased from 12.9% in PD-NC group; 16.7% in PD-MCI group; and 48% in PDD group. Identifying neuropsychiatric symptoms in PD-MCI may have implications for ascertaining conversion to dementia in PD.